Association between Serum Ferritin and Some Bio Variables in Obese Male and Female at Obesity Medical Center in Iraq - Zaizafoon N. Nasif; Emad M. Eltayef; Nasser M. Al-Janabi; Ali N. Niseaf (Disease and Health: Research Developments Vol. 5, 2025)
Obesity is a worldwide health complication. In 2014, 600 million adults and 42 million kids, less than five years of age, were obese. It is a hyperassembly of energy in the form of adipose tissues which has worse effects on health. The major factors of the obesity epidemic are: heavy meal which is rich in lipids, carbohydrates resulting in overweight and eventually obesity, and a decrease in physical activity that leads to defects in calorie conception. In health care facilities ferritin assay is used as a screening test to detect iron deficiency; however, its reliability in obesity has been questioned. The present study aimed to assess and compare the incidence of obesity, hyperferritinemia, hyperlipidemia, and hypouricemia among middle-aged hypertensive patients in the local setting and examined ferritin concentrations and other classical indices in obese males and females. Serum levels of ferritin was assessed using ELISA kit, while Hb was analyzed using Coulter LH 750 Hematology Analyzer and other parameters were assessed by colorimetric kits. This limited population study was conducted at the Obesity Medical Center at Al-Kindy Teaching Hospital, Baghdad, Iraq from January to March 2016. One hindered and eight patients were enrolled in this study plus to participate of 61 subjects as healthy control. Based on body mass index (BMI), 169 participants were divided into two groups: BMI \(\) 18.5-25 kg/m2 non obese (control), BMI \(\) 30 kg/m2 obese subjects. Patients with endocrine disease, pregnancy, and renal disease leading to hypertension were excluded from the study. The statistical package for the social sciences computer program version 20 (IBM SPSS Statistic software, IBM Corporation, New York, United States) was used for the analysis. The main demographic features data of the study population shows that systolic blood pressure and diastolic blood pressure were raised significantly in obese patients (P<0.05) compared with control. Serum hemoglobin levels were decreased significantly in obese males when compared with the non-obese group and no difference in the female group was observed. In addition, the levels of lipid profile and other studied parameters according to gender showed the following results:- significant elevation in TG, LDL, VLDL, glucose, and ferritin in the obese (for both genders) compared with the non-obese group. A significant decrease was noticed in HDL-c, uric acid, and urea levels in the obsessed group compared with the non-obese group in both genders. The comparison results between obese males and females concluded that a significant elevation in BMI with a significant decrease in VLDL and ferritin levels in obese females compared with obese males. The present study examines all types of correlations between parameters. In obese patients (n=108), stepwise linear regression analysis showed that serum ferritin levels were independently correlated with LDL, VLDL levels, and age, (P< 0.001). Increased BMI and ferritin levels are more frequent in females as compared to male obese patients which are an important risk factor for obesity complications.